Aplicación de Instrumentos Internacionales de Derechos Humanos a las personas privadas de la libertad en Colombia (2020)
This article aims to examine some international instruments for the protection of human rights, highlight some of its articles that concern the protection of persons deprived of liberty in Colombia and then make a small study of the reality presented in the centers. Prisoners and penitentiaries, whose radiography has led three times for the Constitutional Court to declare the state of affairs unconstitutional for the massive violation of fundamental rights. The research methodology is documentary and seeks through the doctrinal, jurisprudential, normative and reports consultation, to collect data on the subject that supports the research for an analysis of approximation to the object of study and conclude on the breach of Article 2.2 of the ICCPR and the American Convention. Among the findings, it is worth noting that despite the fact that the Colombian State has signed and ratified international human rights treaties and has issued internal regulations for their protection, there is a constant massive violation of fundamental rights to persons deprived of liberty.